2021
DOI: 10.15252/embj.2020104975
|View full text |Cite
|
Sign up to set email alerts
|

Ythdf is a N6‐methyladenosine reader that modulates Fmr1 target mRNA selection and restricts axonal growth in Drosophila

Abstract: N6‐methyladenosine (m6A) regulates a variety of physiological processes through modulation of RNA metabolism. This modification is particularly enriched in the nervous system of several species, and its dysregulation has been associated with neurodevelopmental defects and neural dysfunctions. In Drosophila, loss of m6A alters fly behavior, albeit the underlying molecular mechanism and the role of m6A during nervous system development have remained elusive. Here we find that impairment of the m6A pathway leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 100 publications
1
67
0
Order By: Relevance
“…In contrast to cluster 1, their m 6 A pattern is dynamic and shifts from bimodal profiles in early stages to a late mostly unimodal m 6 A distribution around the stop codon. Such 5'-enriched m 6 A profiles are observed in plants (Luo et al 2014), Xenopus (Sai et al 2020), mice (Chang et al 2017) and fruit flies (Worpenberg et al 2021) and may be associated to increased RNA turnover and fast transcript processing depending on the positioning of methylation in the CDS or 5'UTR. Consistently, in developing oysters, the early bimodal m 6 A distribution is associated with a low transcript abundance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to cluster 1, their m 6 A pattern is dynamic and shifts from bimodal profiles in early stages to a late mostly unimodal m 6 A distribution around the stop codon. Such 5'-enriched m 6 A profiles are observed in plants (Luo et al 2014), Xenopus (Sai et al 2020), mice (Chang et al 2017) and fruit flies (Worpenberg et al 2021) and may be associated to increased RNA turnover and fast transcript processing depending on the positioning of methylation in the CDS or 5'UTR. Consistently, in developing oysters, the early bimodal m 6 A distribution is associated with a low transcript abundance.…”
Section: Discussionmentioning
confidence: 95%
“…However, despite the developmental significance of m 6 A is conserved across evolution, several differences exist between animal groups. Indeed, in the fruit fly, m 6 A is mostly present in the 5'UTR of mRNAs throughout head and embryo development (Kan et al 2017;Worpenberg et al 2021), whereas methylation enrichment at 5'UTRs promotes cap-independent translation for transcript selection during the stress response in Vertebrates Meyer et al 2015;Coots et al 2017). In the silkworm Bombyx mori, mRNA is mostly m 6 A-methylated in coding sequences (CDS) but not UTRs, and a high methylation is associated with a high gene expression .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several other KH domain-containing proteins, including the fragile X mental retardation protein (FMRP), have been identified in mammalian m 6 A interactome screens as putative m 6 A readers (24,25). However, while it is possible that the KH domain is an evolutionarily conserved m 6 A-binding moiety, it is similarly possible that PfKH.1 is a PfYTH.1-interacting protein, as recently reported in Drosophila melanogaster (26), and thus appears as enriched in the oligonucleotide pulldown experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The FMRP Translational Regulator 1 (FMR1) and Leucine-Rich Pentatricopeptide Repeat-Containing (LRPPRC) proteins can also read m 6 A modifications and affect RNA behavior [48,49]. Recent studies have reported that FMR1 directly interacts with YTHDF1 to inhibit the translation of target transcripts [50].…”
Section: Erasersmentioning
confidence: 99%